2018
DOI: 10.1165/rcmb.2017-0214oc
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived Suppressor Cells Are Necessary for Development of Pulmonary Hypertension

Abstract: Pulmonary hypertension (PH) complicates the care of patients with chronic lung disease, such as idiopathic pulmonary fibrosis (IPF), resulting in a significant increase in morbidity and mortality. Disease pathogenesis is orchestrated by unidentified myeloid-derived cells. We used murine models of PH and pulmonary fibrosis to study the role of circulating myeloid cells in disease pathogenesis and prevention. We administered clodronate liposomes to bleomycin-treated wild-type mice to induce pulmonary fibrosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 69 publications
(70 reference statements)
2
61
0
Order By: Relevance
“…The fact that these non-endothelial cells express CTGF may explain, in part, our findings that after chronic intraperitoneal bleomycin exposure alone (twice weekly for 33 days), eCTGF KO mice were not protected against development of PH (Figure 5B ), or pulmonary fibrosis (Supplementary Figure 1 ). Intriguingly, our group has recently described a novel model for PH, administering bleomycin in combination with clodronate (CL 2 MDP, in figures) liposomes, resulting in depletion of macrophages and robust PH, with nearly no evidence of pulmonary fibrosis (Bryant et al, 2017 ). In light of these findings, we hypothesized that depletion of lung phagocytes with clodronate liposome administration would lead to decreased whole lung CTGF-expression, with a greater dependence on CTGF from the vascular/endothelial compartment in maintaining the wound regulatory balance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that these non-endothelial cells express CTGF may explain, in part, our findings that after chronic intraperitoneal bleomycin exposure alone (twice weekly for 33 days), eCTGF KO mice were not protected against development of PH (Figure 5B ), or pulmonary fibrosis (Supplementary Figure 1 ). Intriguingly, our group has recently described a novel model for PH, administering bleomycin in combination with clodronate (CL 2 MDP, in figures) liposomes, resulting in depletion of macrophages and robust PH, with nearly no evidence of pulmonary fibrosis (Bryant et al, 2017 ). In light of these findings, we hypothesized that depletion of lung phagocytes with clodronate liposome administration would lead to decreased whole lung CTGF-expression, with a greater dependence on CTGF from the vascular/endothelial compartment in maintaining the wound regulatory balance.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, CTGF expression is sufficient to induce bone marrow mesenchymal stem cells/stromal cells to differentiate into collagen-producing fibroblasts, contributing to fibrogenesis and pathological fibrosis (Lee et al, 2010 ). Interestingly, our group has recently described a contributory role of a similarly immature CD11b + myeloid cell population in vascular remodeling necessary for development of chronic hypoxia-induced PH (Bryant et al, 2017 ). A next step in parsing out the mechanistic pathway leading to disease, will involve exploring the CTGF/CD11b interaction in in vitro and in vivo models, to understand the true molecular effect on pathophysiology of pulmonary vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increased expression of endothelial adhesion molecules and proinflammatory cytokines/chemokines, as well as leukocyte recruitment, are also significant features of PH (31,32). Mice deficient in proinflammatory cytokines and endothelial adhesion molecules, as well as those harboring defects in leukocyte recruitment, are not capable of developing severe PH (33)(34)(35). Inflammation, as reflected by the expression levels of proinflammatory cytokines and degree of macrophage infiltration, as well as proliferation of PASMCs, were decreased, along with reduced indices of PH in hypoxic Pfkfb3 +/− mice or 3PO-treated Su/Hx rats.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is perhaps not surprising that one recent study found that elevated concentrations of peripheral blood MDSCs, defined by the surface markers HLA-DR, CD33, CD11b, CD14, and CD66b, reflect poor lung function in patients with IPF ( 118 ). Another experiment with bleomycin-induced mice showed that MDSCs triggered vascular remodeling and pulmonary hypertension, and that preventing their recruitment via neutralization of CXCR2 normalized the pulmonary pressure ( 119 ). While the relationship between vascular abnormalities and parenchymal fibrosis remains poorly understood, accumulating evidence suggests that these events might significantly impact parenchymal homeostasis during injury and repair ( 45 ).…”
Section: Activation Of Professional Immune Cells In Ipf: Pathogen-assmentioning
confidence: 99%